Peningkatan Hasil Belajar Kognitif Siswa Melalui Media Historical Picture Story (HPS) Pada Mata Pelajaran Pendidikan Pancasila Kelas 5 - Nafi’ah, Siti Anisatun; Hidayat, Wahyu; Liandra, Bagas Efri; Mahmudah, Maliha Nur (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2025)
This research aims to improve the cognitive learning outcomes of class 5 students at MI GUPPI At Taqwa Kaliwader in the Pancasila Education subject through the use of Historical Picture Story (HPS) media. The research results showed that the use of HPS media was successful in increasing students' understanding of the historical material on the birth of Pancasila. This can be seen from the increase in the average student score, namely from 34.54 on the pre-test to 56 on the post-test. HPS media helps students understand the material more easily through the visualization of interesting historical images and simple narratives. This media is also suitable for use in schools with limited digital facilities such as projectors. However, this research found obstacles, such as the limited number of HPS media which made it difficult for some students to see images and read text clearly. This shows that HPS media needs to be provided in greater quantities or in a larger format so that it can be accessed by all students equally. Overall, HPS media has proven effective in improving student learning outcomes, especially in understanding abstract concepts such as Pancasila values. The use of learning media such as HPS can be a creative and efficient alternative, especially in school environments with limited facilities. This research recommends increasing the number or variety of HPS media so that learning can be more optimal and provide an enjoyable learning experience for students.